The Next Era of Solid-State Innovation: Beyond Silicon - V. Basil Hans (International Journal of Solid State Innovations & Research, 2025)
The semiconductor industry is getting close to the physical and economic boundaries of silicon-based technology. A new era of solid-state innovation is beginning. Beyond Silicon: The Next Era of Solid-State Innovation looks at the materials, device layouts, and manufacturing methods that are about to change the way electronics and energy work. The article talks about improvements in wide- and ultra-wide-bandgap semiconductors, two- dimensional materials, and quantum and neuromorphic systems that promise better performance, energy efficiency, and features that go beyond what is possible with regular CMOS scaling. It also talks about problems with integration, manufacturability, dependability, and sustainability, and stresses the necessity for interdisciplinary approaches that bring together materials science, physics, and engineering. This article looks at current breakthroughs and future approaches to show how post-silicon technologies could lead to big changes in computing, power electronics, sensing, and communication. These technologies could be the basis for the next generation of solid-state systems. The next phase of solid-state innovation transcends silicon, employing materials such as Gallium Nitride (GaN) and Silicon Carbide (SiC) for enhanced power efficiency, alongside 2D materials like graphene for increased speed. This phase incorporates novel devices (ferroelectrics) for Edge AI, targeting advancements in autonomous systems, accelerated communications (5G/6G), and personalised medicine, transitioning from mere miniaturisation to sophisticated integration and emerging computing paradigms like molecular electronics.In the constantly changing world of semiconductor technology, the quest for smaller and more efficient devices has pushed the limits of materials science and technology. Silicon has been at the centre of the semiconductor industry since the first silicon-based transistor was made in 1947. This is what Moore's Law predicted would happen: computing power would expand at an exponential rate. But as we get closer to the physical and technical boundaries of silicon, the industry faces new problems in keeping up this level of innovation. Silicon's inherent material qualities, which previously helped it rise to the top, now make it hard to move forward in terms of speed, power use, and heat dissipation. So, it has become very important to look for new materials and technologies that can get around these problems while still fulfilling the growing need for more computing power and energy efficiency.
Keywords: Power Consumption; Two- Dimensional (2D) Materials; Wide-Bandgap Semiconductors; and Organic Semiconductors; heat dissipation